The resultative construction with “verbs of cooking” and “verbs of colouring” in English and Spanish: a contrastive lexical-constructional study - Isabel Jiménez Sáez (Estudios de Lingüística)
Despite the extensive interest in cross-linguistic constructional research over the past few decades, the resultative construction in Spanish has largely been overlooked. Unlike its high productivity in English, in Spanish, this construction is confined to very specific contexts such as the culinary or gastronomic scenario or situations involving chromatic change. The present study is contrastive in two senses: on the one hand, it provides a descriptive analysis of the formal and functional differences and similarities of this construction in both languages, and on the other hand, it adopts a lexical-constructional approach combining the theoretical and methodological principles of Goldberg’s (1995) and Boas’s (2003) Construction Grammars. Both principles, traditionally opposed in the literature, aim to determine to what extent the observed properties of the construction under study can be predicted from Goldberg’s generalisations at the constructional level, the event-frame evoked by the predicate as advocated by Boas, or any other factor such as contextual background information or pragmatics. The results of this study are based on the analysis of 1,173 corpus examples of English and Spanish resultative expressions with verbs of cooking and colouring drawn from Levin’s (1993) classification. The data reveal distinctive traits of the Spanish resultative construction with no parallel in English: (i) the unacceptability of inanimate instrument subjects and the prepositional form of the resultative phrase in resultatives with verbs of cooking, (ii) the preference for the prepositional realization of the resultative phrase in examples with verbs of colouring, (iii) the collocational restrictions of the predicates pintar (“paint”) and manchar (“stain”) with regards to the semantic nature of the subject or the form of the RP respectively. In addition, this study demonstrates that finergrained analyses of the predicates’ event-frames, as those put forward by Boas (2003), make it possible to arrive at more accurate predictions about the idiosyncratic properties of each language than Goldberg’s (1995) broad-scale generalizations, some of which have been refuted. Furthermore, it demonstrates that contextual background information largely determines the observed syntactic, semantic, and pragmatic features of the resultative construction.